LEXICAL VARIATION AMONG STANDARD LANGUAGE SPEAKERS IN REPUBLIC OF SRPSKA - Е.И. Јакушкина; Д. Црњак (Filolog, 2023)
This paper is a part of a larger study of regional variation of the lexicon within the Serbian standard language. About 100 questionnaires were collected for this research from educated speakers of the Serbian language from different cities. The questionnaire contains questions which uncover the use of doublets characteristic of the western and eastern parts of the Serbian linguistic territory, such as željezo and gvožđe, mahune and boranija, kino and bioskop. The paper proposes the analysis of around 60 questionnaires from the Republic of Srpska, namely from Banja Luka (47), Trebinje (7), as well as from Prijedor, Bjelina and East Sarajevo. First, the paper presents a list of investigated regional doublets (200 lexemes), and gives their typological division (phonetic or morphological variants, lexical doublets).